Impact of Micro- and Nanocellulose Coating on Properties of Wool Fabric by Using Solution Blow Spinning - Yi Zhang; Abu Naser Md Ahsanul Haque; Maryam Naebe (Fibers)
This study investigates the impact of micro- and nanocellulose coatings on the properties of wool fabrics using the solution blow spinning technique. The objective is to assess how varying cellulose sizes influence key fabric attributes, including physical properties, UV-shielding ability, air permeability and water vapour permeability, with a focus on their practical applications. Coating with microcrystalline cellulose (MCC) was found to increase the air permeability of fabric significantly, whereas coating with cellulose nanocrystals (CNCs) enhanced water vapour permeability and reduced pore size. The air permeability could relate to the breathability, and water vapour permeability could relate to the comfortability. Coated fabric with both sizes of cellulose could have different applications, like pollen filtration and printable cloth, and further functionality could be achieved by modifying the cellulose structure. This research establishes a platform for the effective application of cellulose coatings on wool fabric, offering promising advancements for textile performance and sustainability.